Selective Cytotoxic Activity of Prodigiosin@halloysite Nanoformulation - Guryanov, Ivan; Naumenko, Ekaterina; Akhatova, Farida; Lazzara, Giuseppe; Cavallaro, Giuseppe; Nigamatzyanova, Läysän; Fakhrullin, Rawil (Frontiers in Bioengineering and Biotechnology, 2020)
Prodigiosin, a bioactive secondary metabolite produced by Serratia marcescens, is an effective proapoptotic agent against various cancer cell lines, with little or no toxicity towards normal cells. The hydrophobicity of prodigiosin limits its use for medical and biotechnological applications, these limitations, however, can be overcome by using nanoscale drug carriers, resulting in promising formulations for target delivery systems with great potential for anticancer therapy. Here we report on prodigiosin-loaded halloysite-based nanoformulation and its effects on viability of malignant and non-malignant cells. We have found that prodigiosin-loaded halloysite nanotubes inhibit human epithelial colorectal adenocarcinoma (Caco-2) and human colon carcinoma (HCT116) cells proliferative activity. After treatment of Caco-2 cells with prodigiosin-loaded halloysite nanotubes, we have observed a disorganization of the F-actin structure. Comparison of this effects on malignant (Caco-2, HCT116) and non-malignant (MSC, HSF) cells suggests the selective cytotoxic and genotoxic activity of prodigiosin-HNTs nanoformulation.